Use of lectin-functionalized particles for oral immunotherapy. (February 2012) - Diesner, Susanne C; Wang, Xue-Yan; Jensen-Jarolim, Erika; Untersmayr, Eva; Gabor, Franz
Immunotherapy, in recent times, has found its application in a variety of immunologically mediated diseases. Oral immunotherapy may not only increase patient compliance but may, in particular, also induce both systemic as well as mucosal immune responses, due to mucosal application of active agents. To improve the bioavailability and to trigger strong immunological responses, recent research projects focused on the encapsulation of drugs and antigens into polymer particles. These particles protect the loaded antigen from the harsh conditions in the GI tract. Furthermore, modification of the surface of particles by the use of lectins, such as Aleuria aurantia lectin, wheatgerm agglutinin or Ulex europaeus -I, enhances the binding to epithelial cells, in particular to membranous cells, of the mucosa-associated lymphoid tissue. Membranous cell-specific targeting leads to an improved transepithelial transport of the particle carriers. Thus, enhanced uptake and presentation of the encapsulated antigen by antigen-presenting cells favor strong systemic, but also local, mucosal immune responses.